Psychology and the History of Justice and Human Rights - Niamthong, Patcharawan (Interdisciplinary Journal of Humanities Studies, 2025)
This interdisciplinary academic article aims to analyze and explicate the concepts of justice and human rights through an integration of knowledge from social psychology, political psychology, and the intellectual history of social thought. It emphasizes that justice and human rights are not merely abstract or legal ideals, but are deeply intertwined with human experiences—shaped by learning, emotions, memory, and socio-cultural contexts across different historical periods. The article begins with a historical overview of the idea of justice, from its early appearances in Mesopotamian law and Greek philosophy to the Enlightenment, which gave rise to the modern conception of human rights. It then explores the development of international human rights regimes in the 20th century. Subsequently, it discusses psychological dimensions of justice, including justice sensitivity, moral reasoning, and the emotional drivers—such as anger, empathy, and guilt—that shape human responses to injustice. Furthermore, the article investigates the psychological mechanisms of perpetrators, victims, and bystanders within contexts of human rights violations. It analyzes the role of collective memory in post-crisis social healing, highlighting the significance of public truth-telling, symbolic expressions through art and memorials, and institutional mechanisms such as truth and reconciliation commissions. In addition, the article introduces a structural psychological perspective, drawing on theories such as system justification and ideological cognition, to show how power relations and institutional design can reinforce or challenge social norms surrounding justice and rights. It contends that true justice is not achievable through legal frameworks alone, but must be supported by culturally sensitive institutions and educational processes that foster moral awareness and inclusive participation.The article concludes by proposing that a deeper understanding of justice and human rights requires a psychological lens—one that acknowledges the emotional, cognitive, and social processes involved in their construction. Such an approach holds potential for informing more human-centered policies, education, and reconciliation strategies in diverse socio-political settings.